Evaluation and measurement of primary care services based on patients' experience in China - Chunmei Lin; Sisi Li; Yanchun Zhang; Lifang Zhang; Jiangmei Qin (Chinese General Practice Journal)
Background: Patients' experience is a critical aspect for evaluating the quality of primary care services. However, research on patient experience in China started relatively late, with limited focus on patients in primary care facilities. Objective: To reflect the status of primary care services in China based on the experience of patients visiting primary care facilities. Methods: From March to April 2023, a cross-sectional survey was conducted using intercept sampling in 12 national pilot zones for primary healthcare reform. Investigators, trained in survey techniques, administered the Assessment Survey of Primary Care (ASPC) scale to 1,157 patients at 36 primary care facilities, including township health centers and community health centers. Results: The average scores for five dimensions were: 69.5±20.5 for first visit/first-line care, 74.1±20.1 for service accessibility, 72.0±20.7 for continuity of doctor-patient relationships, 75.1±21.0 for comprehensive services, and 68.5±21.7 for coordinated services. The overall ASPC score was 71.8±17.3. Significant differences (P<0.05) were found based on age, education level, employment status, family doctor enrollment, self-reported chronic conditions and pilot zone. Multivariate regression analysis identified age, employment status, family doctor enrollment, and pilot zone as significant influencing factors for scores in various dimensions. Unemployed patients scored lower across all dimensions compared to employed patients (P < 0.05). Patients with a family doctor contract had higher scores across all dimensions compared to those without a contract (P < 0.05). Significant regional differences in scores were found, with higher scores in Changting and Xishui counties compared to Jiexiu city (P < 0.05), and lower scores in Haiyan, Lu, and Dongfang cities compared to Jiexiu (P < 0.05). Conclusion: The ASPC scale effectively reflects the current state of primary care services in China. The family doctor contracted services improve patient experiences in primary care facilities, particularly in the dimensions of accessibility, doctor-patient continuity, and coordination. Regional variations in patient experiences are linked to “patient-centered” approaches and convenience measures.